Consumer Perception Towards Green Products – A Study With Reference To Chennai City - VIJAYALAKSHMI, Ms. R.; RAMAN, Dr. ANITA (The journal of contemporary issues in business and government, 2021)
Environmentalism has fast emerged as a worldwide phenomenon. Marketing organizations too have risen to the occasion and have started responding to environmental challenges by practicing green marketing strategies. The awareness of Green marketing is increased among the Indian consumers. The present research work indicates that the key to raise green purchasing intention among the general public lies on four factors, which are Attitudes toward the Environment, Social Influence, Health Consciousness and Perceived Consumer Effectiveness. The results of the study it is indicated that green product attributes quality, durability and variety strongly influence the consumers’ understanding and behavior towards environmental friendly features of green products.